Integration Research of Roof High-voltage Electrical Apparatuses for Locomotive and EMUs - Baolin PENG; Ping LIN; Tao LI; Congjian JIANG (机车电传动)
In a heavily polluted environment, high-voltage electrical apparatuses of the locomotive and EMUs easily occur flashover and affect train operation safety. Based on typical locomotives and EMUs main circuit principle, and taking full consideration of safety and maintainability, the high-voltage electrical equipment which was traditionally distributed and installed on the roof of the vehicle were integrated into the enclosed box. The proposal could reduce pollution level of high-voltage electrical apparatuses, improve the insulation reliability of the products, and save the installation space of the equipment in the vehicle.